A INTERNATIONAL JURISDICTION OVER DISPUTES ARISING OUT OF THE CONSUMER CONTRACTS IN THE EUROPEAN UNION LAW - Ristoska, Mirjana; Pelivanova, Natasha (International Scientific Journal Vision, 2017)
As a result of globalization processes, the increased regional integration and the Internet development, the cross-border transactions are among the most common transactions con-cluded nowadays. Consumers conclude international consum-er contracts very often without being aware of it. Consequently, new legal norms have been developed, aiming to protect con-sumers’ rights. Essentially, the main objective of these norms is to protect the consumer as a contracting party, which is in unequal position in relation to the trader, since he does not possess the necessary knowledge and has sufficient funds, in comparison with the trader. This paper analyzes the norms of jurisdiction in disputes aris-ing out of the consumer contracts with a foreign element con-tained in: Regulation (EU) no. 1215/2012 of 12 December 2012 on jurisdiction and the recognition and enforcement of judi-cial decisions in civil and commercial matters (Brussels I Regu-lation - recast) as well as, in the Council Regulation (EC) No. 44/2001 of 22 December 2000 on jurisdiction and the recogni-tion and enforcement of judicial decisions in civil and com-mercial matters (Brussels I Regulation). The main objective of this paper is to research and find out does the norms contained in above mention EU acts are protecting the consumers in sufficient way. To reach this objective the following methods were applied: historical method, method of analysis, normative method, comparative method, case law and Internet research.